Applying fuzzy technique in software team formation based on Belbin team role - Omar, Mazni; Hasan, Bikhtiyar; Ahmad, Mazida; Yasin, Azman; Baharom, Fauziah; Mohd, Haslina; Muhd Darus, Norida (Universiti Teknikal Malaysia Melaka, 2016)
Team roles play significant impact in determining the project success.In order to ensure that team can work together, it is essential to ensure that the team members are assigned to the right role with the right characteristics.One of the prevalent team roles is Belbin team role.The team role can guide project manager to form effective team.However, assigning the correct team role is very challenging.Thus, this study demonstrates the use of fuzzy technique to form a software team based on Belbin team role.By using this technique, it can help decision maker to form effective team that have balance characteristics.In order to validate the proposed technique, future works will be carried out by using empirical data in industrial setting